2003
DOI: 10.1248/cpb.51.359
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chitosan on in Vitro Properties of Eudragit RS Microspheres.

Abstract: Eudragit RS microspheres containing chitosan hydrochloride were prepared by the solvent evaporation method using acetone/liquid paraffin solvent system and their properties were compared with Eudragit RS microspheres without chitosan, prepared in our previous study. Different stirring rates were applied (400-1200 rpm) and drug content, Higuchi dissolution rate constant, surface and structure characteristics of the microspheres were determined for each size fraction. An increase in average particle size with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The stirring speed (X2) showed a slightly negative impact on the %EE. An increase in stirring speed (X2) led to a decrease in %EE, which is accordance with Bozena et al’s work, where they stated that increases in stirring speed will decrease the drug content of particles [ 44 ]. Similarly, JK Patel’s study also showed a decrease of %EE with an increase of stirring speed, which is an accordance with our results [ 45 ].…”
Section: Resultssupporting
confidence: 86%
“…The stirring speed (X2) showed a slightly negative impact on the %EE. An increase in stirring speed (X2) led to a decrease in %EE, which is accordance with Bozena et al’s work, where they stated that increases in stirring speed will decrease the drug content of particles [ 44 ]. Similarly, JK Patel’s study also showed a decrease of %EE with an increase of stirring speed, which is an accordance with our results [ 45 ].…”
Section: Resultssupporting
confidence: 86%
“…Eudragit RL 100 (ERL 100) and Eudragit RS 100 (ERS 100) are inert polymeric resin copolymers of poly(ethacrylate, methylmetacrylate and chlorotrimethyl ammonioethyl methacrylayte) containing an amount of quaternary ammonium groups, ranging between 4.5-6.8% and 8.8-12.0% for RS and RL, respectively. Several reports are cited in the literature on the application of ERS 100 and ERL 100 as polymeric carriers for the delivery of drugs (30)(31)(32)(33). Most of them are for the entrapment of water-insoluble/lipophilic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We are not aware of any published reports on the urea release kinetics for microencapsulated systems using Eudragit RS100®. Eudragit RS100® has been previously studied as an encapsulating agent for drug or selenium delivery . The results obtained in this work for the CSU and ACU microcapsule ammonia‐N release kinetics were favorable, showing an ammonia‐N concentration of 4 mg dL −1 after the first hour.…”
Section: Resultsmentioning
confidence: 64%
“…Although the control group showed accumulation of ammonia‐N in the media, this will not happen in vivo because ammonia‐N is absorbed through the rumen wall into the bloodstream, preventing its accumulation in the rumen fluid . The system consisting only of urea and Eudragit RS100® kept ammonia‐N levels under 8.5 mg dL −1 , perhaps because, during this period, bacteria did not have rapid access to urea as a consequence of being incorporated into the polymerized, granulated structure …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation